Below the Surface : Talking with Teens about Race, Ethnicity, and Identity - Rivas-Drake, Deborah; Umaña-Taylor, Adriana J. (Book collections on Project MUSE., 2019)
A guide to the latest research on how young people can develop positive ethnic-racial identities and strong interracial relationsToday's young people are growing up in an increasingly ethnically and racially diverse society. How do we help them navigate this world productively, given some of the seemingly intractable conflicts we constantly hear about? In Below the Surface, Deborah Rivas-Drake and Adriana Umaña-Taylor explore the latest research in ethnic and racial identity and interracial relations among diverse youth in the United States. Drawing from multiple disciplines, including developmental psychology, social psychology, education, and sociology, the authors demonstrate that young people can have a strong ethnic-racial identity and still view other groups positively, and that in fact, possessing a solid ethnic-racial identity makes it possible to have a more genuine understanding of other groups. During adolescence, teens reexamine, redefine, and consolidate their ethnic-racial identities in the context of family, schools, peers, communities, and the media. The authors explore each of these areas and the ways that ideas of ethnicity and race are implicitly and explicitly taught. They provide convincing evidence that all young people-ethnic majority and minority alike-benefit from engaging in meaningful dialogues about race and ethnicity with caring adults in their lives, which help them build a better perspective about their identity and a foundation for engaging in positive relationships with those who are different from them. Timely and accessible, Below the Surface is an ideal resource for parents, teachers, educators, school administrators, clergy, and all who want to help young people navigate their growth and development successfully.